"Third revolution : population, environment and a sustainable world" - "Harrison, Paul" (New Delhi, 1993)
Harrison argues that population growth, rising consumption and damaging technologies have combined to bring on the biggest environmental crisis in human history. Just as crisis spurred the Agricultural and Industrial Revolutions, so it may the third revolution that is needed to achieve sustainable development. Harrison provides a bulletin on the state of the planet and the process of destruction, and a blueprint for the third revolution. Harrison is author of "Inside the Third World" and was the 1988 recipient of the UNEP Global 500 award for outstanding services to the environment. The book is being made into a TV documentary to coincide with publication.
Keywords: Current events 1991